2024
DOI: 10.1186/s13018-023-04497-8
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram based on high-density lipoprotein cholesterol for the occurrence of preoperative deep vein thrombosis in patients with intertrochanteric femur fracture: a retrospective study

Wencai Li,
He Ling,
Rongbin Lu
et al.

Abstract: Background This study aims to develop a nomogram and forecast the incidence of DVT in individuals suffering from an intertrochanteric femur fracture. Method This work created a nomogram using the R programming language and employed logistic regression to determine independent predicting features. An external validation dataset was used to validate the nomogram. Result The findings demonstrated the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…One study found higher levels of lactate in fresh venous thrombi rich in red blood cells [25], suggesting that higher lactate levels are associated with higher mortality rates in LEDVT patients, consistent with the results of this study. In three retrospective studies, lymphocytes were found to be a risk factor for DVT [26][27][28] . lymphocytes also play an important role in the body's immune system, and abnormally elevated lymphocytes levels may indicate a potential viral infection, leading to a decrease in platelet count and further aggravating LEDVT, increasing the risk of mortality.…”
Section: Rivaroxaban and Enoxaparin Are Both Clinically Used For The ...mentioning
confidence: 99%
“…One study found higher levels of lactate in fresh venous thrombi rich in red blood cells [25], suggesting that higher lactate levels are associated with higher mortality rates in LEDVT patients, consistent with the results of this study. In three retrospective studies, lymphocytes were found to be a risk factor for DVT [26][27][28] . lymphocytes also play an important role in the body's immune system, and abnormally elevated lymphocytes levels may indicate a potential viral infection, leading to a decrease in platelet count and further aggravating LEDVT, increasing the risk of mortality.…”
Section: Rivaroxaban and Enoxaparin Are Both Clinically Used For The ...mentioning
confidence: 99%